The Variability of Winds and Fluxes Observed Near Submesoscale Fronts. Issue 11 (16th November 2019) - Shao, Mingming; Ortiz‐Suslow, David G.; Haus, Brian K.; Lund, Björn; Williams, Neil J.; Özgökmen, Tamay M.; Laxague, Nathan J. M.; Horstmann, Jochen; Klymak, Jody M.
Abstract: Submesoscale oceanic fronts (SFs), which typically occur on a spatial scale of 0.1–10 km, may have a large influence on the atmospheric surface layer (ASL). However, due to their short temporal‐spatial scales, evaluating their direct impact on this layer remains challenging and characterizing the nature of SF‐ASL interaction has not been done in the field. To address this, a study of the air‐sea response to SFs was conducted using observations collected during the Lagrangian Submesoscale Experiment, which took place in the northern Gulf of Mexico. This manuscript focuses on the meteorological measurements made from a pair of masts installed on the bow of the R/V Walton Smith . This work represents one of the first observation‐based investigations into the potential influence that SFs have on the ASL. Contemporaneous measurements from an X‐band marine radar, moving vessel profiler, and Lagrangian drifters were also used to analyze the SF dynamics. Systematic surface wind velocity changes over several cross‐frontal transects were observed, a process previously associated with mesoscale fronts. A comparison between the eddy covariance and parameterized (COARE 3.5) air‐sea fluxes revealed that the directly observed heat flux was 1.5 times larger than the bulk value in the vicinity of the SFs. This suggests that the hydrodynamic processes near the front enhance the local exchange of sensible and latent heat. Given the prevalence of SF over the global upper ocean, these findings suggest that these features may have a widely distributed and cumulative impact on air‐sea interactions. Plain Language Summary: The atmosphere responds to the ocean over all scales—from microscopic to planetary scales. Previous studies showed that surface wind and even the entire atmospheric boundary layer could be affected by the relatively large‐scale (10–1, 000 km) temperature variations across the open ocean, for example, the Gulf Stream. However, the impacts of relatively small‐scale (100 m to 10 km) and rapidly (hours to days) evolving fronts are largely unknown due to the difficulty in actually observing the physical processes. As part of an ongoing effort to better understand surface material dispersion across the northern Gulf of Mexico, we conducted ship‐based measurements of air‐sea fluxes across near small‐scale fronts. The observations showed that the physical mechanism used to explain the interaction between the atmosphere and large‐scale ocean temperature gradients readily downscales to these smaller fronts, which have a direct impact of wind directly above the ocean surface. These small‐scale fronts were also observed to locally enhance the air‐sea heat flux, and the conventional model used to predict this underestimates the observed value by as much as 50%. These small‐scale frontal features are common across the global ocean, and our findings suggest that they could cumulatively impact the global energy budget. Key Points: Systematic ship‐based observations of wind and fluxes across submesoscale fronts were conducted in varying wind directions Cross‐frontal wind variance depended on the airflow relative to the in‐water thermal gradient Submesoscale fronts were observed to locally enhance air‐sea heat flux, compared to values from commonly used bulk algorithm